1990
DOI: 10.1002/j.1460-2075.1990.tb08297.x
|View full text |Cite
|
Sign up to set email alerts
|

Raising the intracellular level of inositol 1,4,5-trisphosphate changes plasma membrane ion transport in characean algae.

Abstract: Inositol 1,4,5‐trisphosphate (InsP3) was introduced into the cytoplasm of characean algae in two different ways: (i) by iontophoretic injection into cytoplasm‐enriched fragments from Chara and (ii) by adding InsP3 to the permeabilization medium of locally permeabilized cells of Nitella. In both systems this operation induced a depolarization of the membrane potential, ranging from a few mV to sequences of action potentials. The effect of InsP3 on locally permeabilized Nitella cells was abolished when InsP3 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…These reveal that plants possess the key proteins and mechanisms for a stimulus-induced and IP 3 -mediated mobilization of Ca 2+ from internal stores (Sanders, Brownlee & Harper, 1999;Reddy, 2001). Also Chara cells most likely have such a signalling system, because it was shown that electrophoretic injection of IP 3 triggered membrane excitation (Thiel, MacRobbie & Hanke, 1990), while inhibition of phospholipase C abolished excitability of these cells (Biskup et al, 1999).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These reveal that plants possess the key proteins and mechanisms for a stimulus-induced and IP 3 -mediated mobilization of Ca 2+ from internal stores (Sanders, Brownlee & Harper, 1999;Reddy, 2001). Also Chara cells most likely have such a signalling system, because it was shown that electrophoretic injection of IP 3 triggered membrane excitation (Thiel, MacRobbie & Hanke, 1990), while inhibition of phospholipase C abolished excitability of these cells (Biskup et al, 1999).…”
Section: Resultsmentioning
confidence: 97%
“…A large body of experimental evidence has precluded that voltage-dependent Ca 2+ influx via plasma membrane channels can be the primary source for the rise in Ca 2+ during excitation in Chara (Homann & Thiel, 1994;Thiel et al, 1997;Plieth et al 1998;Wacke & Thiel, 2001). The experimental data on the dynamics of ½Ca 2þ cyt as well as on the gating of the Ca 2+ -sensitive Cl À channels, which produce the depolarization of the action potential, can be best explained by a model in which a voltage-dependent production of a second messenger (Homann & Thiel, 1994;Thiel & Dityatev, 1998;Wacke & Thiel, 2001), most likely IP 3 (Thiel et al, 1990;Biskup et al, 1999), is triggering the release of Ca 2+ from internal stores. The above analysis of a combined model for voltagedependent production of such a second messenger and Ca 2+ mobilization from internal stores by IP 3 and Ca 2+ now allows successful simulation of the aforementioned body of experimental observations in the context of electrical excitation in plants.…”
Section: Resultsmentioning
confidence: 99%
“…Findlay & Hope 1964;Lunevsky et al, 1983;Kataev, Zherelova & Berestovsky, 1984;Caldwell, Van Brunt & Harold, 1986;Shiina & Tazawa, 1988;Thiel, MacRobbie & Hanke, 1990; see also Tester, 1990); only very recently has attention turned to the presence of Cl-channels in traditionally nonexcitable higher-plant cells (Falke et al, 1987(Falke et al, , 1988Schauf & Wilson, 1987;Fairley & Walker, 1989; see also Okazaki & Tazawa, 1990). It is all the more striking, therefore, that a dominant theme among the recent discoveries is the role of Ca 2 + in activating or modulating channel current (Boult et al, 1989;Schroeder & Hagiwara, 1989;.…”
Section: Gating Of the K ~ Inward Rectifier Is Sensitive To H +mentioning
confidence: 92%
“…IP 3 and cyclic ADP-ribose induces Ca 2ϩ release in Euglena gracilis microsome fractions in a dose-dependent manner (61). In the giant algae Chara corallina and Nitrella translucens, IP 3 produces action potentials involving increased [Ca 2ϩ ] i (93). Treatment of vacuolar membrane vesicles from Candida albicans with IP 3 results in Ca 2ϩ release, blocked by heparin and ruthenium red (14).…”
Section: Camentioning
confidence: 99%